2012
DOI: 10.1104/pp.112.196717
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stresses of Field Growth Allow Cinnamyl Alcohol Dehydrogenase-Deficient Nicotiana attenuata Plants to Compensate for their Structural Deficiencies      

Abstract: The organized lignocellulosic assemblies of cell walls provide the structural integrity required for the large statures of terrestrial plants. Silencing two CINNAMYL ALCOHOL DEHYDROGENASE (CAD) genes in Nicotiana attenuata produced plants (ir-CAD) with thin, red-pigmented stems, low CAD and sinapyl alcohol dehydrogenase activity, low lignin contents, and rubbery, structurally unstable stems when grown in the glasshouse (GH). However, when planted into their native desert habitat, ir-CAD plants produced robust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 120 publications
0
51
0
Order By: Relevance
“…However, it was reported recently that Nicotiana attenuata plants with silenced CAD gene, had robust phenotype when grown in a greenhouse, but showed normal phenotype when planted in a field [19]. It was found that down-regulation had not regressed, only various compounds where inbuilt in lignin structure to ensure up-right orientation of the stalk.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was reported recently that Nicotiana attenuata plants with silenced CAD gene, had robust phenotype when grown in a greenhouse, but showed normal phenotype when planted in a field [19]. It was found that down-regulation had not regressed, only various compounds where inbuilt in lignin structure to ensure up-right orientation of the stalk.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors have been shown previously to interact with CAD deficiency in CAD-deficient M. truncatula: the phenotype of these plants was equal to that of the wild type when grown at ambient temperatures, but the plants were dwarfed when grown at elevated temperatures (30°C; Zhao et al, 2013). In contrast, down-regulating CAD in Nicotiana attenuata produced plants with thin and structurally unstable stems when grown in the greenhouse, but the normal phenotype was restored when plants were grown outdoors (Kaur et al, 2012). Hence, it is important to investigate how the hpCAD poplars with this level of lignin alteration will respond when grown in the field, especially regarding biomass and bioethanol yield.…”
Section: Cad1 Down-regulation Does Not Affect Plant Yield Under Greenmentioning
confidence: 93%
“…Rather than anthocyanins, as in petunia ir-PhCCoAOMT1 plants, changes in coloration in poplar were due to the accumulation of hydroxycinnamic acids. Similarly, silencing of CINNAMYL ALCOHOL DEHYDROGENASE, acting downstream of CCoAOMT1 in the monolignol pathway, resulted in a reddish xylem in Nicotiana attenuata plants due to the accumulation of hydroxycinnamaldehydes (Kaur et al, 2012). Interestingly, more benzoic acid (C 6 -C 1 )-related compounds accumulated in poplar (p-hydroxybenzoate attached to lignin) and Arabidopsis (four benzenoic hexose esters) when CCoAOMT expression was reduced.…”
Section: Discussionmentioning
confidence: 99%